Modelling bicycle route choice using data from a GPS-assisted household survey - Ghanayim, Muhammad; Bekhor, Shlomo (European Journal of Transport and Infrastructure Research, 2018)
This paper considers bicycle route choice for commuter trips. Bicycle route preferences are analysed using a dataset from a GPS-assisted household travel survey conducted in the Tel Aviv metropolitan area. Different choice set generation methods were applied to generate alternative routes for each observation, and the matching with the actual route is discussed. Model estimation is performed for different route choice sets to test the sensitivity of the parameter estimates. The results obtained are quite consistent, and indicate an expected tendency to ride in longer routes, but with separated bike lanes. In the absence of such lanes, riders prefer to use local streets and avoid riding on busy arterial streets and highways.